2015
DOI: 10.1016/j.cellimm.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Toll-like receptor 9 attenuates sepsis-induced mortality through suppressing excessive inflammatory response

Abstract: Sepsis, a major clinical problem with high morbidity and mortality, is caused by overwhelming systemic host-inflammatory response. Toll-like receptors (TLRs) play a fundamental role in induction of hyperinflammation and tissue damage in sepsis. In this study, we demonstrate a protective role of TLR9 inhibition against the dysregulated inflammatory response and tissue injury in sepsis. TLR9 deficiency decreased the mortality of mice following cecal ligation and puncture (CLP) -induced sepsis. TLR9 knockout mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…We therefore assessed the phosphorylation of AKT in the spleen of vehicle- and human ghrelin-treated mice in sepsis. Similar to a recent finding on the p-AKT level in the spleen of murine CLP-induced sepsis [ 31 ], we also found that sepsis significantly downregulated p-AKT level in the spleen, while the mice treated with human ghrelin significantly increased p-AKT level by 21% as compared to the vehicle-treated septic mice ( Fig 8 ).…”
Section: Resultssupporting
confidence: 91%
“…We therefore assessed the phosphorylation of AKT in the spleen of vehicle- and human ghrelin-treated mice in sepsis. Similar to a recent finding on the p-AKT level in the spleen of murine CLP-induced sepsis [ 31 ], we also found that sepsis significantly downregulated p-AKT level in the spleen, while the mice treated with human ghrelin significantly increased p-AKT level by 21% as compared to the vehicle-treated septic mice ( Fig 8 ).…”
Section: Resultssupporting
confidence: 91%
“…org/10.1172/JCI127542DS1; refs. [18][19][20]. However, the mechanisms underlying the protection resulting from TLR9 suppression in sepsis are unclear.…”
Section: Tlr9 Signaling In Fibroblastic Reticular Cells Regulates Permentioning
confidence: 99%
“…Previous studies have shown that genetically and pharmacologically blocking TLR9 alleviates inflammation, organ damage, and mortality in mouse polymicrobial sepsis models (18)(19)(20). However, the mechanisms underlying the protective roles of TLR9 inhibition are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of p38- and ERK-dependent pathways is associated with splenic, pulmonary, and hepatic inflammation 42–44 . Endothelial dysfunction and coagulopathy have also been found to be mediated by these pathways 42–44 .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of p38- and ERK-dependent pathways is associated with splenic, pulmonary, and hepatic inflammation 42–44 . Endothelial dysfunction and coagulopathy have also been found to be mediated by these pathways 42–44 . A conceptual challenge of pharmaceutical approaches directed at specific signaling elements is the diversity of signaling molecules that participate in inflammation signaling.…”
Section: Discussionmentioning
confidence: 99%